2014
DOI: 10.1093/mutage/geu041
|View full text |Cite
|
Sign up to set email alerts
|

Multicolour FISH analysis of ionising radiation induced micronucleus formation in human lymphocytes

Abstract: Micronucleation of chromosomal DNA is an effective indicator of DNA damage and micronucleus (MN) analysis is a valuable tool for radiation biodosimetry studies. To gain a comprehensive knowledge of micronucleation process after ionising radiation (IR) exposure, whole genome-wide chromosome analysis is desirable. With this objective, multicolour fluorescence in situ hybridization (M-FISH) technique was utilised in the present study to characterise the chromosome content of spontaneous and IR-induced micronuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…The authors concluded that not all chromosomes in the human genome are equally susceptible to micronucleation. Balajee et al [ 12 ] confirmed results of Walker et al [ 11 ] on frequent involvement of larger chromosomes in radiation-induced MN. The authors consider that “frequencies of chromosomes micronucleation seem to correlate well with chromosome size because of a higher probability of double-strand breaks induction owing to spatial and temporal organization of chromatin in the interphase nuclei”.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The authors concluded that not all chromosomes in the human genome are equally susceptible to micronucleation. Balajee et al [ 12 ] confirmed results of Walker et al [ 11 ] on frequent involvement of larger chromosomes in radiation-induced MN. The authors consider that “frequencies of chromosomes micronucleation seem to correlate well with chromosome size because of a higher probability of double-strand breaks induction owing to spatial and temporal organization of chromatin in the interphase nuclei”.…”
Section: Discussionsupporting
confidence: 60%
“…Random involvement of chromosomes in radiation-induced MN, depending on the DNA content, was shown by [ 10 ]. Other studies demonstrated both random and non-random incorporation of DNA from different chromosomes in radiation-induced MN, larger chromosomes being usually overrepresented in the MN content [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study utilized the multicolor FISH technique to identify the chromosomes involved in micronuclei formation after radiation exposure. [ 18 ] Recently, a new high-throughput and miniaturized CBMN method was also established for rapid processing a large number of samples (in about 3 days), a critical requirement for radiological triage. [ 19 20 ] Since the CBMN assay, unlike the DCA, can be easily performed and analyzed without an extensive cytogenetic expertise, many laboratories routinely use the CBMN assay for dose estimation.…”
Section: Cytokinesis-block Micronucleus Assaymentioning
confidence: 99%
“…The minimum dose is dependent on study endpoints, and the smaller the minimum dose, the more sensitive the endpoint. Studies of chromosomal aberration and micronucleus formation, ( 7 12 ) as well as mutation and transformation assays, ( 13 , 14 ) are sensitive approaches that utilize small doses of approximately 0.1 Gy (100 mGy). However, it remains controversial whether or not the dose-effect relationship is linear at lower doses, according to linear non-threshold (LNT), or non-LNT theory.…”
Section: Introductionmentioning
confidence: 99%